Investigating Vaccine Hesitancy in Canada: A Quantitative and Qualitative Description of Vaccine Attitudes, Beliefs, and Perceptions of the Seasonal Influenza Vaccine. - Perna, Andrea (Université d'Ottawa / University of Ottawa, 2016)
The overarching objective of this thesis was to investigate the phenomenon of vaccine hesitancy in Canada and examine relationships among vaccine beliefs, socio-demographic characteristics, and seasonal influenza immunization. Quantitative findings were derived from a national health risk perception survey administered to adults across Canada (N = 1,125). Respondents were asked to provide their level of agreement (1 = do not agree at all to 5 = agree completely) with 2 vaccine-related behaviour statements and 21 vaccine-related beliefs statements. A principal components analysis was performed to reduce the number of belief statements into meaningful components. Two components were retained and reflected negative beliefs about ‘vaccine safety’ and positive beliefs about ‘vaccine regulation and benefits’. Descriptive results presented in the first study indicated a heightened uncertainty about the long-term side effects of vaccination, particularly with respect to the purported link between the Measles-Mumps-Rubella vaccine and the development of autism, among survey respondents. Multivariate analyses identified differences in the endorsement of numerous vaccine beliefs according to age and educational attainment. Findings revealed that older respondents and respondents without a university education demonstrated more negative attitudes towards vaccination, whereas younger respondents and respondents with a university education demonstrated more positive vaccine attitudes, respectively. Finally, both components of vaccine beliefs were significant predictors of vaccine-related behaviours, including discussing information about vaccines with others and reported receipt of the seasonal influenza vaccine. The second study investigated interrelationships among components of vaccine beliefs, socio-demographic characteristics, and reported receipt of the seasonal influenza vaccine. A mediation analysis revealed that higher levels of agreement with the statement ‘I usually get the seasonal flu vaccine’ among older adults was associated with lower levels of agreement with negative beliefs about vaccine safety in conjunction with higher levels of agreement with positive beliefs about the regulation and benefits of vaccines, whereas the opposite was true for younger adults. Also, a significant moderation analysis revealed that among respondents with greater concern about vaccine safety, those with higher educational attainment reported lower levels of agreement with the statement ‘I usually get the seasonal flu vaccine’ compared to those with lower educational attainment. Recognizing the limitations of quantitative findings, a qualitative investigation was undertaken to provide more in-depth insight on the factors driving influenza immunization among healthy adults. A thematic analysis was performed on transcripts from 6 semi-structured focus group discussions with a total of 18 participants residing in Ottawa, Ontario. Findings identified 7 themes and 8 sub-themes related to contextual, vaccine specific, and individual determinants of vaccine hesitancy. Participants predominantly discussed themes related to individual determinants of vaccine hesitancy (perceived severity, susceptibility, and likelihood of contracting the influenza virus; personal interests; interactions with healthcare professionals). The perceived novelty, severity and effectiveness of the influenza vaccine, as well as a lack of information and discontent with communication by government health authorities and the media were also discussed. Overall, findings identified salient themes informing vaccine decision-making and behaviours among a sample of educated adults, which can inform subsequent studies investigating influenza immunization in a more representative sample of Canadian adults.
Keywords: Vaccine hesitancy; risk perception; seasonal influenza; immunization